The Mediating Role of Mental Agility in Healthcare Professionals’ Perception of Digital Competence and General Attitudes Toward Artificial Intelligence (Third Sector Social Economic Review, 2026)
The aim of this research is to determine the impact of healthcare professionals' digital competencies on their general attitudes toward artificial intelligence and to reveal the mediating effect of the concept of "mental agility," a sub-dimension of learning agility, in the relationship between these concepts. Within the scope of the research, 468 healthcare professionals working in private-public health complexes in Istanbul were reached. In the study, Cronbach’s Alpha, KMO and Bartlett, CR, and AVE values were examined to test the validity and reliability of the variables. A correlation analysis was conducted to reveal the relationship and direction between the research variables. Structural Equation Modeling was utilized to test the research hypotheses. When the analyzes conducted within the scope of the research were examined, it was observed that health professionals' perceptions of digital competence had a significant positive effect on their general attitude toward artificial intelligence, perceptions of digital competence had a significant positive effect on mental agility, and mental agility had a significant positive effect on their general attitude toward artificial intelligence. The path analysis results conducted for the main purpose of the research determined that mental agility has a "partial mediating effect" in the relationship between digital competence and the general attitude toward artificial intelligence. The research results indicate that the digital competencies of healthcare professionals not only accept artificial intelligence but also indirectly nurture mental skills and agility processes. The mediating effect of mental agility proves that it indirectly enhances the adaptation processes of healthcare professionals related to digital competence and artificial intelligence.
Keywords: Healthcare Workers; Digital Competence; Artificial Intelligence; Mental Agility; Structural Equation Modeling; Mediating Role